(untitled) (Journal of Namibian Studies : History Politics Culture, 2020)
The National Assembly and Presidential election results of 27 November 2019 suggest a turning point in Namibia’s democracy. For the first time since the UN-supervised elections prior to Independence in 1990, the dominant party and its presidential candidate lost votes. Despite remaining firmly in political power, the emergence of new political actors has modified the political contestations with possibly lasting impacts. This analysis recapitulates the trends and considers some of the contributing factors to the new constellation in the political sphere. It explores the implications and consequences for President Hage Geingob’s second term in office and takes a closer look at the new Cabinet and related governance structures.